The Impact of Color, Content, and Feeling of Empathy on Website Visitors’ Intentions to Support an NPO: The Moderated Mediation Role of Need for Social Status - Saenz, Camila; Liu, Yulun; Jiang, Hanling (Journal of Computational and Cognitive Engineering, 2024)
Nonprofit organizations (NPOs) are undergoing a gradual transformation to adapt to the demands of the modern era. One of the key challenges they face is harnessing the power of social media and online donations effectively, a task made even more daunting for smaller- and medium-sized NPOs operating on limited budgets. In response to this challenge, an experimental study was conducted, focusing on the intersection of website and advertisement design with principles of consumer psychology. This study involved a scenario-based experiment that engaged 452 participants from the United States. The results of the experiment unveiled a significant and intriguing interplay between the use of color and content in shaping online donation intentions and the inclination to share website links. Crucially, this dynamic was found to be mediated by the perceived level of empathy experienced by visitors to NPO websites, which in turn was influenced by their individual desires for social status. The findings offer actionable insights for NPO managers and designers alike. By aligning their website design with customer preferences, NPOs can cost-effectively enhance their online presence. This, in turn, fosters increased engagement on social media platforms and encourages a surge in online donations, facilitating a smooth transition for NPOs into the digital age. In a world where online visibility and fundraising capabilities are vital for NPOs’ sustainability, this research provides a valuable roadmap for their continued success and impact. Received: 23 August 2023 | Revised: 12 October 2023 | Accepted: 21 November 2023 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data available on request from the corresponding author upon reasonable request.